A novel optimized neural network model for cyber attack detection using enhanced whale optimization algorithm - Koganti Krishna Jyothi; Subba Reddy Borra; Koganti Srilakshmi; Praveen Kumar Balachandran; Ganesh Prasad Reddy; Ilhami Colak; C. Dhanamjayulu; Ravikumar Chinthaginjala; Baseem Khan (Scientific Reports, 2024)
Abstract Cybersecurity is critical in today’s digitally linked and networked society. There is no way to overestimate the importance of cyber security as technology develops and becomes more pervasive in our daily lives. Cybersecurity is essential to people’s protection. One type of cyberattack known as “credential stuffing” involves using previously acquired usernames and passwords by attackers to access user accounts on several websites without authorization. This is feasible as a lot of people use the same passwords and usernames on several different websites. Maintaining the security of online accounts requires defence against credential-stuffing attacks. The problems of credential stuffing attacks, failure detection, and prediction can be handled by the suggested EWOA-ANN model. Here, a novel optimization approach known as Enhanced Whale Optimization Algorithm (EWOA) is put on to train the neural network. The effectiveness of the suggested attack identification model has been demonstrated, and an empirical comparison will be carried out with respect to specific security analysis.